Analysis of Audience Reception of Habib Ja’far's Dawah on the LOGIN Close The Door Event - Anggrainy, Septy; Kunaeni; Hasyim Maulidah, Nur (Jurnal Al Nahyan, 2025)
Social media has become an integral part of people's lives, including in the method of preaching. In the millennial era, preachers or religious scholars utilize YouTube as one of the most important parts of their preaching strategy. One of the underlying aspects of this research is to delve into public opinion regarding the preaching of Habib Ja’far in the program LOGIN Close The Door. The research adopts a Qualitative Descriptive method, employing the theory of audience reception analysis. In utilizing this theory, the researcher focuses on the community's opinions regarding the preaching conducted by Habib Ja’far on YouTube in the program Login Close The Door. Data collection techniques include observation and documentation, utilizing both primary and secondary data sources.